O lado ruim das marcas: uma escala de mensuração comportamental das relações negativas do consumidor com a marca - Rodrigues, Luis Adriano (2021)
There is a growing need to understand both the positive aspects that make a consumer interested in a particular product and brand, and the negative aspects of a consumer's relationship with a brand and how they happen. However, it is difficult to measure this, mainly because there is not a complete conceptual consensus on the negative relationships of the consumer with the brand, as well as a scale capable of measuring such relationships was not found. Thus, this thesis has the objective of creating a scale to measure the behavior related to the negative relationships of the consumer with the brand – NCBBR. Therefore, the procedures suggested by Churchill (1997) for the construction of scales were used as inspiration in the research: 1 – domain of the construct, for this, a survey of the theoretical framework was carried out; 2 – item development, in this phase a systematic literature review was carried out, a meeting with experts, a focus group, and the creation of variables; 3 - data collection; 4 – purity measures, using Pearson's correlation; 5 – reliability assessment, using Cronbach's Alpha and Extracted Mean Variance; 6 – assessment of discriminant and convergent validity, Exploratory Factor Analysis and Confirmatory Factor Analysis; 7– development of norms for the future replication of the work. It is noteworthy that in carrying out the steps of quantitative data collection, the survey method was adopted, in which a collection was applied, only with higher education students or who are studying in higher education. The final scale has 38 variables, reaching the appropriate indices in the final model, contemplating the following behaviors: Brand Divorce, Anti-Brand Consumption, Vindictive Complaining, Third Party Complaining, Negative Word of Mouth, Third Party Complaining for resolution, Problem Solving Complaining and Anti- Brand Activism. In this sense, this thesis proposes a holistic scale to measure consumer behavior with the brand arising from negative relationships with it.